El desarrollo y la fisonomía del Derecho socialista - Escobar Córdoba, Federico (2023)
This article purports to recover Socia list Law as a subject in both Comparative Law and Legal History. True to this goal, most of the article presents a panoramic vision of Socialist Law. In or der to do so, the author synthesizes the historical development of the Soviet Un ion, describes socialist attitudes toward the State and Law, and summarizes the debate about the place Socialist Law should have among other legal systems of the world. Later, in a final section, the paper underscores the importance of in terdisciplinary studies of concepts like “legal culture,” with the aim of strengthening the analysis of legal influence in general and of the influe nce of Socialist Law in particular.